2010
DOI: 10.1124/jpet.109.164210
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Membrane Component 1 (Pgrmc1): A Heme-1 Domain Protein That Promotes Tumorigenesis and Is Inhibited by a Small Molecule

Abstract: Tumorigenesis requires the concerted action of multiple pathways, including pathways that stimulate proliferation and increase metabolism. Progesterone receptor membrane component 1 (Pgrmc1) is related to cytochrome b 5 , binds to heme, and is associated with DNA damage resistance and apoptotic suppression. Pgrmc1 is induced by carcinogens, including dioxin, and is up-regulated in multiple types of cancer. In the present study, we found that Pgrmc1 increased in vivo tumor growth, anchorage-independent growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
151
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 36 publications
8
151
2
1
Order By: Relevance
“…These results are in broad agreement with those obtained by Ahmed et al (2010a,b) using cancer cells, where PGRMC1 was shown to bind to EGFR and stabilize it on the plasma membrane, whereas AG205 decreased EGFR expression. Treatment with AG205 also inhibited cancer cell growth in these studies which is consistent with the known roles of both PGRMC1 and EGFR in promoting cancer growth and progression (Ono & Kuwano 2006, Ahmed et al 2010b. Thus, PGRMC1 acts as an adaptor protein regulating EGFR expression on the cell membranes of normal and malignant cells and promotes EGFR-dependent signaling in both health and disease.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…These results are in broad agreement with those obtained by Ahmed et al (2010a,b) using cancer cells, where PGRMC1 was shown to bind to EGFR and stabilize it on the plasma membrane, whereas AG205 decreased EGFR expression. Treatment with AG205 also inhibited cancer cell growth in these studies which is consistent with the known roles of both PGRMC1 and EGFR in promoting cancer growth and progression (Ono & Kuwano 2006, Ahmed et al 2010b. Thus, PGRMC1 acts as an adaptor protein regulating EGFR expression on the cell membranes of normal and malignant cells and promotes EGFR-dependent signaling in both health and disease.…”
Section: Discussionsupporting
confidence: 70%
“…Results of subsequent studies have indicated that AG205 binds to PGRMC1 and has a similar effect to that observed after treatment with Pgmrc1 siRNA in lung cancer cells, decreasing phosphorylation of ERK (Ahmed et al 2010b). Treatment with AG205 also decreases EGFR-dependent signaling in lung cancer cells, consistent with the proposed role of PGRMC1 as a binding partner with EGFR (Ahmed et al 2010a).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…PGRMC1 expression is elevated in several cancer cells like lung, breast, and ovarian cancer (3)(4)(5). Further, in ovarian cancer PGRMC1 expression is increased in advanced cancer stages (3).…”
Section: Introductionmentioning
confidence: 96%